Investigate the strength and weaknesses of cooperative learning strategy according to the students' perception in the IX grade of SMK Nurul Ma'arif Boarding Scool Sintang - Aditya, Denuk (Universitas Jambi, Magister Program of English Education Department, 2022)
This research is aimed to find out the influence of Student Team Achievement Division (STAD) learning model on students' English skills ability in English Language lesson. This research is conducted in the IX grade students in the SMK Nurul Ma’arif Sintang, province of West-Borneo. The research uses the qualitative descriptive design. The study sample consists of 30 students of XI grade. The results of the research show that: (1) as a whole, students' ability in English language lesson with STAD learning model is highly influenced based on student perception. (2) There is an influence of interaction between STAD learning model on students' ability in english lesson. From the findings of the study, it is concluded that the STAD model has an influence on students' ability in English language lesson in the XI grade students in SMK Nurul Ma’arif Sintang